Development of crop water production model in a rainfed tropical maize crop cultivation - Balogun, L. A.; Ewemoje, T. A.; Aderemi, M. A.; Nasirudeen, A. R.; Lasisi, D.; Hammed, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Crop production, which is one of the sources of food for human and animal sustenance is a function of the availability of adequate quantity of water. The rainfall being seasonal is the main source of water for agricultural production in Nigeria. Maize production is majorly through rainfed agriculture in Nigeria and the irregularity of which affect the yield. This research work was to develop crop-water production model in tropical rain fed maize crop cultivation using maize yield and rainfall data from Oyo state. One of the major problems of food production in attempting to determine the relative future roles of irrigated and rain-fed agriculture is the lack of sufficient ground and accurate tool on a localized basis. Hence, the essence of this research works. Using correlation and full quadratic regression analysis, the effects of some rainfall indices (monthly and annual rainfall, raindays, and rainfall onset and rainfall cessation) on maize yield in Oyo State were examined. The results of the correlation statistics showed that cessation has the strongest association (r= - 0.284) with maize yield. The analysis also showed that early maize and late maize suffer moisture deficiency in March and November respectively while excessive rainfall of June/July and September also have implication for maize yield.  It was also observed that the rainfall characteristics jointly contributed 96.7% in explaining the variations in the yield of maize per hectare. Conclusively, a model was development for predicting maize yield in Oyo State. The study also recommends the use of state own yield so as to harmonize with state rainfall data, application of appropriate moisture conservation management practices that ensured efficient use of water and use of drought resistance crop species with shorter growing periods as adaptive measures to the changing rainfall pattern within the study area.